2010
DOI: 10.1002/sia.3367
|View full text |Cite
|
Sign up to set email alerts
|

An XPS study of the interatomic charge distribution in stainless steels

Abstract: The secondary spectral feature of the Al Kα-excited Ni 2p spectrum, positioned at a kinetic energy of approximately 6 eV lower than the main Ni 2p peak, is known as either the 2p satellite (in the case of inorganic materials) or a plasmon loss peak (in the case of metals). This feature was used to probe changes in the local electronic structure of Ni in stainless steels. The results were compared with a previous study on Auger parameter and core-core-valence (CCV) Auger lines acquired using Cu Kα radiation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…induces a positive shift in XPS spectra [32]. Therefore, the drastic shift induced by carbon may not be attributed to the adsorption of carbon on the surface but a solid solution of carbon into the nickel lattice, because the interstitial type of solid solution as in the case of the current study is known to decrease the binding energy of the system, resulting in a negative shift in the XPS spectra [33][34][35]. In fact, a number of reports in the literature have implicitly indicated that a solid solution has a significant influence on the changes in surface energies [36][37][38][39].…”
Section: Methodsmentioning
confidence: 69%
“…induces a positive shift in XPS spectra [32]. Therefore, the drastic shift induced by carbon may not be attributed to the adsorption of carbon on the surface but a solid solution of carbon into the nickel lattice, because the interstitial type of solid solution as in the case of the current study is known to decrease the binding energy of the system, resulting in a negative shift in the XPS spectra [33][34][35]. In fact, a number of reports in the literature have implicitly indicated that a solid solution has a significant influence on the changes in surface energies [36][37][38][39].…”
Section: Methodsmentioning
confidence: 69%
“…The easy access to the Fe1s and Cr1s core levels with the CuKα source was used for detailed studies of charge redistribution in the alloying that takes place in the manufacture of stainless steels. 51,52 A study of the plasmon losses associated with the Fe1s spectrum was also undertaken. 53 The benefits of combining XPS using a higher energy source with conventional XPS (AlKα) were also demonstrated in the study of a series of vanadium 54 and titanium 55 compounds.…”
Section: Copper Kα Xpsmentioning
confidence: 99%
“…The easy access to the Fe1s and Cr1s core levels with the CuKα source was used for detailed studies of charge redistribution in the alloying that takes place in the manufacture of stainless steels 51,52 . A study of the plasmon losses associated with the Fe1s spectrum was also undertaken 53 .…”
Section: Monochromatic Sources For Higher Energy Xpsmentioning
confidence: 99%
“…In Ref. [92,93], extensive XPS and AES analyses were undertaken on several Cr-Ni alloyed steels to investigate the local charge variation phenomena taking place at the atomic level, which was claimed to have dominant effect on the local atomic potential. In brief, because of the difference electronegativeness of Cr, Fe and Ni, Cr acts as a cation in the Fe-Cr-Ni system to donate electrons to Fe whereas Ni attracts electrons from Fe.…”
Section: Structural-chemical Characterization By Mossbauer Spectroscopymentioning
confidence: 99%